Ferritic Stainless Steels Coated a Dense La0.7Sr0.3CrO3 Layer as Interconnects for SOFCs - Zhang, Luhe; Bao, Weitao (Asian Journal of Chemistry, 2013)
The La0.7Sr0.3CrO3 (LSC) powders were prepared using liquid-solid reaction method. The LSC ceramic layer was coated by plasma spraying on ferritic stainless steels to form a dense LSC film to resist high temperature oxidation corrosion. The results show the crystal phase of the coated layer is perovskite structure and the LSC coated layer is dense and the mass loss of the interconnects is 0.3 mg/cm2 after heating at 850 ºC for 60 h.